Platelet-Adherent Leukocytes Associated With Cutaneous Cross-Reactive Hypersensitivity to Nonsteroidal Anti-Inflammatory Drugs - Jurado-Escobar, Raquel; Doña, Inmaculada; Bogas-Herrera, Gador; Pérez-Sánchez, Natalia; Salas, María; Laguna, José J.; Muñoz-Cano, Rosa; Mayorga, Cristobalina; Torres, María J.; Cornejo-García, José A. (Frontiers in Pharmacology, 2020)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most highly consumed drugs worldwide and the main triggers of drug hypersensitivity reactions. The most frequent reaction, named cross-reactive NSAID-hypersensitivity, is due to the pharmacological activity of these drugs by blocking the COX-1 enzyme. Such inhibition leads to cysteinyl-leukotriene (CysLTs) synthesis, mainly LTE4, which are responsible for the reaction. Although the complete molecular picture of the underlying mechanisms remains elusive, the participation of platelet-adherent leukocytes (CD61+) and integrins have been described for NSAID-exacerbated respiratory disease (NERD). However, there is a lack of information concerning NSAID-induced urticaria/angioedema (NIUA), by far the most frequent clinical phenotype. Here we have evaluated the potential role of CD61+ leukocytes and integrins (CD18, CD11a, CD11b, and CD11c) in patients with NIUA, and included the other two phenotypes with cutaneous involvement, NSAID-exacerbated cutaneous disease (NECD) and blended reactions (simultaneous skin and airways involvement). A group NSAID-tolerant individuals was also included. During the acute phase of the reaction, the three clinical phenotypes showed increased frequencies of CD61+ neutrophils, eosinophils, and monocytes compared to controls, which correlated with urinary LTE4 levels. However, no correlation was found between these variables at basal state. Furthermore, increased expressions of CD18 and CD11a were found in the three CD61+ leukocytes subsets in NIUA, NECD and blended reactions during the acute phase when compared with CD61- leukocyte subpopulations. During the acute phase, CD61+ neutrophils, eosinophils and monocytes showed increased CD18 and CD11a expression when compared with CD61+ leukocytes at basal state. No differences were found when comparing controls and CD61+ leukocytes at basal state. Our results support the participation of platelet-adherent leukocytes and integrins in cutaneous cross-hypersensitivity to NSAIDs and provide a link between these cells and arachidonic acid metabolism. Our findings also suggest that these reactions do not involve a systemic imbalance in the frequency of CD61+ cells/integrin expression or levels of LTE4, which represents a substantial difference to NERD. Although further studies are needed, our results shed light on the molecular basis of cutaneous cross-reactive NSAID-hypersensitivity, providing potential targets for therapy through the inhibition of platelet-leukocyte interactions.